Treatment of Primary Hyperoxaluria. Issue 244 (December 1970) - Dent, C. E.; Stamp, T. C. B.
Abstract : Nine patients with primary hyperoxaluria have been followed regularly for 1 to 11 years, and their treatment and progress are discussed in relation to the known natural history of the disease. 6 of them probably have the usual form of primary hyperoxaluria associated with increased glycollic acid excretion, while 3 who are sibs have the recently described variant associated with L-glyceric aciduria and normal glycollic acid excretion. All 9 patients have been on regimens designed to increase the urinary solubility of calcium oxalate, with or without the simultaneous lowering of urinary calcium and raising of urinary phosphate excretions. 8 patients have been treated for 1½-7½ years (average duration 4 years) with oral magnesium hydroxide, and 2 patients have been treated with sodium phosphate. One of the latter was changed after 3½ years to magnesium hydroxide and the other has been on sodium phosphate combined with a low calcium diet and cellulose phosphate continuously for 5½ years. 2, not at first diagnosed as hyperoxalurics, were first given sodium bicarbonate for their presumably secondary renal tubular acidosis. The over-all progress of the whole group is felt to have been better than could be expected from the known natural history of primary hyperoxaluria. They average 4¼ years on treatment during 5 years of our observation and all remain clinically well after an average of 9½ years since the onset of their first symptoms. Results warrant the recommendation that, until reliable means are available to decrease oxalate over-production, affected patients should be treated continuously with magnesium hydroxide. A more final opinion must await many more years of follow-up. The failure of several attempts to lower urinary oxalate excretion in these patients is also reported.